Unregulated Health Research Using Mobile Devices: Ethical Considerations and Policy Recommendations. Issue 1 (March 2020) - Rothstein, Mark A.; Wilbanks, John T.; Beskow, Laura M.; Brelsford, Kathleen M.; Brothers, Kyle B.; Doerr, Megan; Evans, Barbara J.; Hammack-Aviran, Catherine M.; McGowan, Michelle L.; Tovino, Stacey A.
Mobile devices with health apps, direct-to-consumer genetic testing, crowd-sourced information, and other data sources have enabled research by new classes of researchers. Independent researchers, citizen scientists, patient-directed researchers, self-experimenters, and others are not covered by federal research regulations because they are not recipients of federal financial assistance or conducting research in anticipation of a submission to the FDA for approval of a new drug or medical device. This article addresses the difficult policy challenge of promoting the welfare and interests of research participants, as well as the public, in the absence of regulatory requirements and without discouraging independent, innovative scientific inquiry. The article recommends a series of measures, including education, consultation, transparency, self-governance, and regulation to strike the appropriate balance.